THE PROBLEM OF ECONOMIC PERFORMANCE IN THE INTERPRETATION OF ISLAM (SOCIAL PHILOSOPHICAL ANALYSIS) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The concept of stability can have different meanings in different contexts. In general, stability refers to the ability of a certain state or system to remain in place for a long period of time. Economic stability is the ability of the economy to be resistant to changes and maintain long-term development opportunities. These include low and stable inflation, employment, equitable income distribution and economic growth.